Обзор перспективных методов рециркуляции уранав ядерно-топливном цикле; Известия вузов. Физика; Т. 58, № 2-2 - Орлов А. А. Алексей Алексеевич; Кравченко А. В. Алёна Владимировна; Титов Е. С. Евгений Сергеевич; Лебедев А. Я. Альберт Яковлевич (2015, 2015)
Заглавие с экрана